Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1519/jsc.0b013e31823b0a5a
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an In-Helmet Temperature Monitor System to Rectal Temperature During Exercise

Abstract: Body temperature monitoring is crucial in helping to decrease the amount and severity of heat illnesses; however, a practical method of monitoring temperature is lacking. In response to the lack of a practical method of monitoring the temperature of athletes, Hothead Technologies developed a device (HOT), which continuously monitors an athlete's fluctuations in body temperature. HOT measures forehead temperature inside helmets. The purpose of this study was to compare HOT against rectal temperature (Trec). Mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…Wickwire et al (15) , using the same device tested in the present study, concluded that an in-helmet measurement system provided a reasonable representation of T c , especially at higher temperatures. Gunga et al (17) also found similar results with a device placed inside a firefighter's helmet.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…Wickwire et al (15) , using the same device tested in the present study, concluded that an in-helmet measurement system provided a reasonable representation of T c , especially at higher temperatures. Gunga et al (17) also found similar results with a device placed inside a firefighter's helmet.…”
Section: Discussionsupporting
confidence: 56%
“…A likely reason for the differences in the conclusions of the aforementioned studies is the presence of the insulation effect created by placing the sensor inside a helmet, thus creating a heated microenvironment; a condition identified by Wickwire et al (15) The hardhat cavity temperatures observed in the current study at the end of exercise indicate that the environment inside the hardhat reaches temperatures that are relatively high; in fact, greater than Tsk. The insulation effect is accentuated when the sensor is held against the skin by the supporting band of the hardhat, as was the case in the present study.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations